The Effect of Work Discipline on Employee Performance at the Sinjai Regency Food Security Service - Suriani; Anwar; Agung Widhi Kurniawan; Abdi Akbar; Uhud Darmawan Natsir (International Humanity Advance, Business & Sciences, 2023)
The role of human resources is essential for an organization. In line with the development of the globalization era, all organizations/institutions are demanded to carry out their tasks responsibly to achieve good performance. One of the factors influencing this performance is work discipline. The purpose of this research is to determine the effect of work discipline on the performance of employees at the Food Security Agency of Sinjai Regency. The research population consists of all 32 employees of the Food Security Agency of Sinjai Regency. The sampling method used is saturated sampling, where all 32 employees are taken as samples. The data from the questionnaires were processed using SPSS version 26.0 software.